The Socio-Cultural Capital of Successful Villages - Luther, Daniel (Institute of ethnology and social athropology SAS, 2021)
This publication is dedicated mainly to experts and people interested in issues concerning life in the countryside that can be a source of knowledge. It is also dedicated to the current political establishment that should specifically deal with rural problems. Not with society as an imaginary whole, but on a differentiated basis, as the countryside in its diversity (as well as small or larger towns) have specific problems and needs. Analyses made by expert teams and knowledge of the development of society are usually summarised in the form of common tables and statements, but do not reflect at all the reality of life in the countryside. We wish that - let's say - for economic or environmental reasons, fields, meadows or pastures are not overgrown with shrub and that they are maintained and bring economic benefit to their owners. The question is how effective agricultural policy tools are in lowland municipalities with large land plots and a favourable climate compared to mountainous municipalities with restricted and harsher conditions. How can entrepreneurs or farmers grow crops on lands in dead-end, mountainous or hillside municipalities compared to lowland areas? Experts in this field would definitely be able to ask many more questions about positive developments in the Slovak countryside. In this publication, we do not wish to highlight only the deficiencies of managing the Slovak countryside, but also to show positive examples from municipalities that have been able to develop despite their problems and enable their citizens to live a dignified life.